Discussion on the combustion, performance and emissions of a dual fuel diesel engine fuelled with methanol-based CeO2 nanofluids. (15th October 2021) - Pan, Suozhu; Wei, Jiangjun; Tao, Changfa; Lv, Gang; Qian, Yejian; Liu, Qiang; Han, Weiqiang
Highlights: The presence of nano-CeO2 in methanol increased peak HRRmax and Pmax. Nano-CeO2 additives promoted a shorter ignition delay and combustion duration. Nano-CeO2 additives in methanol increased BTE and lessened BSFC and EGT. Nano-CeO2 inclusion in methanol can suppress CO, HC, NOX and smoke emissions. Abstract: This paper signifies the effects of cerium oxide (CeO2 ) nanoparticles on the combustion, performance and emissions characteristics of a dual fuel diesel engine under different loads. The stable methanol-based nanofluids with the dispersion of 25 ppm and 100 ppm of CeO2 nanoparticles fuels (MCN25 and MCN100) were prepared by ultrasound and surfactant. The tests were conducted on a dual fuel diesel engine under three modes: diesel mode, by injecting diesel alone into the cylinder; methanol mode, with methanol intake manifold injection and diesel direct injection; and MCN mode, with MCN fuels intake manifold injection and diesel direct injection. The results show that the peak heat release rate and the peak cylinder gas pressure in MCN mode are increased by 7.9% and 4.3% compared to those of diesel mode. Compared to methanol mode, the engine operated in MCN mode effectively reduces brake specific energy consumption by a maximum of 8.1% and increases brake thermal efficiency by up to 10.8%. Further, the increased HC and CO emissions in methanol mode (compared to diesel mode) are suppressed effectively when adding CeO2 nanoparticles in methanol, with the maximum reductions of 56.3% and 79.8% in HC and CO emission for the dosage of 100 ppm, respectively. Compared with diesel mode, the engine operated in methanol mode can decrease the NOX emission and smoke opacity, while more significant reductions can be observed with the addition of CeO2 nanoparticles in methanol, with the maximum decreasing results of 70.9% and 90.3%.